Comparación de cuatro protocolos anestésicos para ovariohisterectomia canina en jornadas de esterilización masiva (2007)
ABSTRACT: Four anesthetic protocols were evaluated for ovariohysterectomy in twenty female dogs. The bitches were randomly divided in four groups of five animals each and were assigned to one of four different anesthetic protocols. In all the protocols xylazine, acepromacine and atropine were included in preanesthesia; ketamine was added to groups 3 and 4 in premedication. Induction was made with ketamine in groups 1 and 4, or propofol in groups 2 and 3. Three anesthesiological variables (latency period, length of the anesthesia and recovery from anesthesia) and six physiological variables (body temperature, cardiac frequency, respiratory frequency, diastolic and systolic blood pressure, oxygen saturation in blood, carbon dioxide in exhaled air) were evaluated. For analysis of data a fully random - balanced fix effect - experimental design, with five replications for treatment was used. The Tukey test with 95% confidence intervals was used for analysis of quantitative variables. A unidirectional descriptive analysis was also used. Body temperature decreased up to 37 ºC in all animals in group 1. The respiratory frequency showed a great variation, especially in groups 1 and 2 (without ketamine in premedication), being more stable in protocol 3 (propofol without ketamine) (p<0.05). Cardiac frequency was slightly increased in group 1. Oxygen saturation in blood and carbon dioxide in exhaled air were stable and similar in all groups (within physiological limits). Systolic and diastolic blood pressures were stable with propofol, higher with ketamine in preanesthesia and induction, and unstable when ketamine was used in induction only. The anesthesiological variables evaluated did not show statistically significant differences among the four protocols. Based on the clinical behavior and on the physiological variables, it was concluded that, the use of ketamine and propofol (protocol 3) for preanesthesia and induction, respectively, is the best anesthetic combination for massive neutering of bitches.